2020
DOI: 10.1002/smtd.202000556
|View full text |Cite
|
Sign up to set email alerts
|

Conversion Reaction Mechanism for Yolk‐Shell‐Structured Iron Telluride‐C Nanospheres and Exploration of Their Electrochemical Performance as an Anode Material for Potassium‐Ion Batteries

Abstract: materials for SIBs. [10-12] Zhang et al. reported on the Na-ion storage activity of CoTe 2 based on the redox mechanism. [10] They found that CoTe 2 nanocrystals transformed into metallic Co and Na 2 Te during the discharge process and the CoTe 2 phase was reversibly formed during repeated cycles. A composite of CoTe 2 and graphene also exhibited excellent gravimetric and volumetric Na ion storage performance. Sun et al. found that layered NiTe 2 nanoparticles anchored on carbon nanosheets exhibit ultrafast an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 51 publications
0
33
0
1
Order By: Relevance
“…In principle, the value of b = 0.5 stands for a typical diffusion‐controlled behavior, whereas a value of b = 1 implies a surface‐induced capacitive process. [ 49 ] In Figure 6b, the b values of five peaks are 0.95, 0.82, 0.96, 0.98, and 0.81, respectively, telling us that the whole redox kinetics of ZnCoSe@NDC electrode are mainly controlled by the surface capacitance‐dominated behavior. Moreover, the ratio of capacitive contributions can be quantified comply with the formulas below [ 50 ] i = k1 v+k2v1/2 …”
Section: Resultsmentioning
confidence: 96%
“…In principle, the value of b = 0.5 stands for a typical diffusion‐controlled behavior, whereas a value of b = 1 implies a surface‐induced capacitive process. [ 49 ] In Figure 6b, the b values of five peaks are 0.95, 0.82, 0.96, 0.98, and 0.81, respectively, telling us that the whole redox kinetics of ZnCoSe@NDC electrode are mainly controlled by the surface capacitance‐dominated behavior. Moreover, the ratio of capacitive contributions can be quantified comply with the formulas below [ 50 ] i = k1 v+k2v1/2 …”
Section: Resultsmentioning
confidence: 96%
“…While for the conversion electrodes, Kang and colleagues synthesized yolk‐shell FeTe 2 ‐C anode and subjected to in situ EIS to explore the conversion reaction mechanism for the electrode. [ 48 ] They suggested that the total resistance ( R tot ) of FeTe 2 ‐C consist of the interface resistance ( R suf ) and the charge transfer resistance ( R ct ). But it was difficult to distinguish resistance components.…”
Section: Electroanalytical Methodsmentioning
confidence: 99%
“…c) Variation in K + diffusion coefficient of FeTe 2 -C. Reproduced with permission. [48] Copyright 2020, Wiley-VCH. d) Nyquist plots in KFSI.…”
mentioning
confidence: 99%
“…Intercalation‐conversion materials mainly consist of transition metal compounds, which mainly include oxides, 104‐106 sulfates, 107‐109 selenides, 110,111 and tellurides 112,113 with the reaction of M a X b + (b.n)K ↔ K bn M a X b ↔ a M + b K n X for PIBs. M denotes the transition metal like Fe, Co, Ni, Mo, Re, and so on, X denotes the anion (O, S, Se, Te, etc .…”
Section: Carbon‐based Composite Materials For Potassium‐ion Batteriesmentioning
confidence: 99%